Investigation of mental endurance levels of canoe athletes in sport: a cross-sectional study - Levent Tanyeri; Hakan Kırkbir; İsmet Çinan; Büsra Yilmaz; Serkan Hacıcaferoğlu (Physical Education of Students)
Background and Study Aim. Mental endurance is considered a key psychological component that influences athletic performance, particularly in sports that demand high levels of focus and persistence. The aim of the study was to investigate the level of mental endurance in athletes engaged in canoeing.